Developing context-related recommendations for best practice in technology-enhanced learning, teaching and assessment - Sibusiso Mdletshe; Jonathan McNulty; John Sandars (University of Johannesburg, 2018)
Background: The use of technology-enhanced learning, teaching and assessment (TELTA) requires consideration of the local context in addition to the pedagogical aspects. Aim: The aim of this project was to develop context-related recommendations for best practice in TELTA to ensure effective design and delivery in South Africa and the Global South. Methods: A systematic inquiry approach with an iterative parallel process: • Part 1 - literature review with considerations of the local context • Part 2 - engagement of industry experts and the visit to the site identified as the best practice Results: A best practice model with five sequential steps was developed: • Reason for the use of the technology • Identification of the knowledge to be taught with technology • Consideration of pedagogical theories • Identification of the suitable technology • Design the learning activity Conclusion: The proposed best practice model simplifies the process of using TELTA.